생체 내 티타늄과 지르코니아 표면에서 형성시킨 치면세균막의 비교 - 임규택; 이지현; 임일구; 박소현; 임현필; 김옥수; Lim, Kyu-Taek; Lee, Ji-Hyun; Lim, Il-Gu; Park, So-Hyun; Lim, Hyun-Phil; Kim, Ok-Su (Taehan Chikwa Poch'ol Hakhoe chi, 2013)
Purpose: This study was conducted to compare in vivo biofilm formation on titanium surface and zirconia surface. Materials and methods: For biofilm formation on titanium and zirconia in oral cavity, after producing oral appliances using acrylic resin and orthodontic wire tailored to 9 subjects, we made titanium and zirconia specimens ($6mm{×}6mm{×}2mm$), fixed them on oral appliances and maintained them in oral cavity of test subjects for 24 and 72 hours. Test subjects who have equipped two pairs of specimens maintained oral hygiene not by using toothpaste but only by tooth brushing. After 24 and 72 hours, we removed and observed specimens through scanning electron microscopy (SEM). Results: Biofilm formation showed large deviation depending on individuals. For formation comparison between titanium and zirconia for 24 hours, zirconia showed less biofilm formation than titanium. Biofilm formation showed large deviation depending on individuals. As for formation comparison between zirconia and titanium, the degree of biofilm formation in zirconia was less than it was in titanium after a lapse of 24 hours. The result of biofilm formation in 72 hours trial show that zirconia has an inclination to formate less biofilm than it was in titanium. Conclusion: Based on the above results, we can conclude that early biofilm formation in oral cavity was influenced by difference of abutment materials. 연구 목적: 본 연구는 생체 내 티타늄과 지르코니아 표면에 치면세균막의 형성 정도를 비교하기 위함이다. 연구 재료 및 방법: 티타늄과 지르코니아의 구강 내 치면세균막의 형성을 위해 구강 내 장치를 아크릴릭 레진과 교정용 와이어를 이용하여 9명의 실험대상자에 맞추어 제작한 후 티타늄과 지르코니아 봉을 일정 크기의 시편 ($6mm{×}6mm{×}2mm$)으로 만들어 장치에 고정하여 실험 대상자 구강 내에 24시간, 72시간 유지시켰다. 2쌍으로 만들어 장치한 시편을 실험 대상자는 치약 등의 구강세정제를 사용하지 않고 잇솔질만으로 구강위생을 유지하였다. 24시간, 72시간 경과 후 시편을 제거하여 SEM (주사전자 현미경)으로 치면세균막을 관찰하였다. 결과: 주사전자현미경의 결과 치면세균막의 형성 정도는 개인의 특성에 따라 큰 편차를 보였고, 24시간 후 치면세균막의 비교했을 때 지르코니아 표면에서 치면세균막의 형성 정도가 티타늄의 표면에 비해 적었다. 72시간 후 치면세균막의 형성 정도는 티타늄 표면보다 지르코니아 표면에서 적은 경향을 보였다. 결론: 구강 내에서 치면세균막의 초기 형성은 지대주 소재의 차이에 의해 영향을 받을 것으로 생각된다.